Ophthalmomyiasis Externa and Importance of Risk Factors, Clinical Manifestations, and Diagnosis: Review of the Medical Literature - Hugo Martinez-Rojano; Herón Huerta; Reyna Sámano; Gabriela Chico-Barba; Jennifer Mier-Cabrera; Estibeyesbo Said Plascencia-Nieto (Diseases, 2023)
Objective: This review aims to describe and compare the risk factors, clinical course, diagnosis, and parasitologic features of external ophthalmomyiasis. We also discuss the different preventive measures and the effect of global warming in a large case series reported from January 2000 to December 2022. Methods: We perform a literature review of reported cases of external ophthalmomyiasis to determine the clinical characteristics, therapeutic management, and information on the organisms that most commonly cause external ophthalmomyiasis. Results: A total of 312 cases of external ophthalmomyiasis were recorded. The most common causative organism was Oestrus ovis (Linnaeus) (Diptera: Oestridae), accounting for 72.1% of cases, followed by Dermatobia hominis (Linnaeus Jr. in Pallas, 1781) (Diptera: Oestridae) at 5.4%, Lucilia sericata (Meigen) (Diptera: Calliphoridae) at 0.96%, and Chrysomyia bezziana (Villeneuve) (Diptera: Calliphoridae) at 0.96%. Before experiencing symptoms, 43.6% of cases reported having direct contact with flies or being hit in the eye, 33% reported no associated risk factors, 9.3% reported living with sheep and goats, and 7.7% reported a history of foreign objects entering the eye. The most common symptoms for those affected by O. ovis were sudden onset, including a foreign body sensation and movement, redness, tearing, itching, swelling, irritation, photophobia, burning, and ocular secretion. In cases caused by D. hominis, symptoms included eyelid edema, pain, redness, itching, movement within the lesion, ocular irritation, and discharge. Regarding occupational or recreational activity, agriculture, and livestock had the highest incidence, followed by trades and technical activities, being a student, and having traveled to an endemic region for work or recreation. Conclusion: Patients with red eyes may suffer from external ophthalmomyiasis, which requires a thorough examination to diagnose and treat it early. Moreover, as the temperature increases due to climate change, it is essential to consider how this will affect the spread of different pathogens.